Sikap Agen Perubahan Guru Dan Karyawan Di SMKS Dhuafa Padang - Delia Reski Annisa; Tesha Syahwani Putri (CV. ITTC INDONESIA, 2025)
This observation examines the attitudes of teachers and staff as agents of change at SMKS Dhuafa Padang. Teachers and staff play a crucial role in driving positive change in the school environment, making it more adaptive and innovative. Direct observation and interviews were used to capture their attitudes in carrying out these roles. Observations indicate that teachers actively initiate change through the development of learning methods and effective communication with students and colleagues. Staff also contribute by providing effective service and supporting the smooth running of school activities. Motivational leadership and a collaborative work culture are key supporting factors. Challenges identified include limited facilities and resistance to change. Efforts to address these barriers include training, improved communication, and strengthening work morale. This study confirms that positive attitudes of teachers and staff as agents of change are crucial for creating a dynamic and competitive school.